The Pseudomonas type III effector HopQ1 activates cytokinin signaling and interferes with plant innate immunity. Issue 2 (11th October 2013) - Hann, Dagmar R.; Domínguez‐Ferreras, Ana; Motyka, Vaclav; Dobrev, Petre I.; Schornack, Sebastian; Jehle, Anna; Felix, Georg; Chinchilla, Delphine; Rathjen, John P.; Boller, Thomas
Summary We characterized the molecular function of the Pseudomonas syringae pv. tomato DC3000 (Pto) effector HopQ1. In silico studies suggest that HopQ1 might possess nucleoside hydrolase activity based on the presence of a characteristic aspartate motif. Transgenic Arabidopsis lines expressing HopQ1 or HopQ1 aspartate mutant variants were characterized with respect to flagellin triggered immunity, phenotype and changes in phytohormone content by high‐performance liquid chromatography‐MS (HPLC‐MS). We found that HopQ1, but not its aspartate mutants, suppressed all tested immunity marker assays. Suppression of immunity was the result of a lack of the flagellin receptor FLS2, whose gene expression was abolished by HopQ1 in a promoter‐dependent manner. Furthermore, HopQ1 induced cytokinin signaling in Arabidopsis and the elevation in cytokinin signaling appears to be responsible for the attenuation of FLS2 expression. We conclude that HopQ1 can activate cytokinin signaling and that moderate activation of cytokinin signaling leads to suppression of FLS2 accumulation and thus defense signaling.